Prediction model to determine natural frequency for integral abutment bridge: a simplified method - Ibrahim, Muhammad Khairil (2015)
All bridges can be resonated with certain frequencies known as modal frequency. Different bridges will have their own natural frequencies depending on their types, parameters and configurations. In order to overcome this phenomenon, the engineer should ensure that the natural frequencies of the bridge to be within 1.5 Hz to 4.5 Hz which are the normal vibration induced by the vehicle. Therefore, it is necessary to have a reliable model to predict the natural frequency of an integral bridge when this type of bridge is a commonly being used this day. Whilst most of the previous researches have been focusing on predicting the natural frequencies of other types of bridges, less research can be found for integral bridges. The effect of span length with clay soil is discussed in this paper and the final expression is presented and verified.